1997
DOI: 10.1007/s00585-997-0943-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric source region of discrete auroras inferred from their relationship with isotropy boundaries of energetic particles

Abstract: Abstract. According to observations, the discrete auroral arcs can sometimes be found, either deep inside the auroral oval or at the poleward border of the wide (socalled double) auroral oval, which map to very di erent regions of the magnetotail. To ®nd common physical conditions for the auroral-arc generation in these magnetotail regions, we study the spatial relationship between the di use and discrete auroras and the isotropic boundaries (IBs) of the precipitating energetic particles which can be used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 34 publications
5
39
1
Order By: Relevance
“…Such consistency is unlikely to be fortuitous only. As a matter of fact, the above result is fully consistent with a number of existing observations and theoretical proposals that an equatorward-most arc likely maps to somewhere in the earthward portion of a stretched thin current sheet, on the verge of a transition into the quasidipolar inner magnetosphere (Lui and Burrows, 1978;Galperin et al, 1992;Yahnin et al, 1997;Galperin and Bosqued, 1999;Sergeev et al, 2012). In particular, using an event-adaptive magnetic field model (Kubyshkina et al, 2011) tuned by THEMIS, GOES, and NOAA observations, Sergeev et al (2012) mapped the prebreakup arc to the CPS, and found that the AR was situated at the outer edge of a "magnetic wall" region with strong B z and R c gradient.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Such consistency is unlikely to be fortuitous only. As a matter of fact, the above result is fully consistent with a number of existing observations and theoretical proposals that an equatorward-most arc likely maps to somewhere in the earthward portion of a stretched thin current sheet, on the verge of a transition into the quasidipolar inner magnetosphere (Lui and Burrows, 1978;Galperin et al, 1992;Yahnin et al, 1997;Galperin and Bosqued, 1999;Sergeev et al, 2012). In particular, using an event-adaptive magnetic field model (Kubyshkina et al, 2011) tuned by THEMIS, GOES, and NOAA observations, Sergeev et al (2012) mapped the prebreakup arc to the CPS, and found that the AR was situated at the outer edge of a "magnetic wall" region with strong B z and R c gradient.…”
Section: Discussionsupporting
confidence: 89%
“…Compared to the above-inferred location of the earthward boundary of AR at ∼ 05:11 UTC; X ∼ −6.7; R ∼ 9.8 R E , even taking into account a slow migration of the NTR during the two measurement epochs, we are able to deduce the following key inference on the relative location of the AR with respect to the NTR: the AR itself is embedded in a highly stretched current sheet region with a relatively stable B z , but its earthward edge is on the verge of a transition into a quasi-dipolar magnetosphere with much steepened B z gradients. The above inference of the AR location is fully consistent with a number of existing observations and theoretical proposals that an equatorward-most arc likely maps to the earthward portion of a stretched current sheet region, at the periphery of the quasi-dipolar magnetosphere (Lui and Burrows, 1978;Galperin et al, 1992;Yahnin et al, 1997;Galperin and Bosqued, 1999;Sergeev et al, 2012).…”
Section: April 2009 Eventsupporting
confidence: 88%
“…The region where precipitation flux is over 10 0 mW/m 2 is identified as auroral oval, whereas that where the flux is below the value is identified as subauroral region (Yahnin et al 1997). In this manner, we selected only subauroral region flows.…”
Section: Discussionmentioning
confidence: 99%
“…Early in situ observations of CS thinning around x =−10 to −12 R E in the near-Earth magnetosphere [Mitchell et al, 1990;Pulkkinen et al, 1991;Sergeev et al, 1993;Sanny et al, 1994] and estimates of equatorial magnetic field gradients from precipitation models [Sergeev et al, 1990;Yahnin et al, 1997] suggested that CS thickness can decrease to 500-1000 km (see, also, review by Ganushkina et al [2015]). This scale is comparable to or even smaller than the local ion gyroradius.…”
Section: Introductionmentioning
confidence: 99%